Digital workflow in prosthodontics/restorative dentistry - de Queirós, José Lincoln; Ottoboni, Thiago; Urbano, Gabriel S.; Bianchi, Danilo M.; Sartori, Renato; No-Cortes, Juliana; Lima, Jacqueline F.; Markarian, Roberto A.; Costa, Alan J.M.; Burgoa, Shaban M.; Melo, Charles; Sesma, Newton; et al. (Wiley, 2022)
This chapter covers the main digital workflow techniques currently used in the field of prosthodontics and restorative dentistry. Dental technologists who become computer-aided design (CAD) technicians can usually also help to integrating the different steps of digital restorative dentistry. Intraoral scanning can be limited by mouth opening, size of scanning device, and adjacent oral structures. The virtual articulator is a digital tool with a function similar to the physical articulator, that is, to analyze the dynamics of the occlusion. In implant dentistry, abutments represent connections between implant-supported crowns and fixtures. The fabrication of complete-arch fixed implant supported prostheses (CAFIP) depends on precise treatment steps involving the rehabilitation planning, implant installation, clinical and laboratory prosthetic procedures. The development of CAD-computer-aided manufacturing systems, dedicated materials, equipment, and software has extended the prosthetic outcome possibilities and workflow options for CAFIPs.
Keywords: Complete-arch fixed implant supported prostheses; Computer-aided design technicians; Computer-aided manufacturing systems; Digital workflow techniques; Intraoral scanning; Virtual articulator